2017
DOI: 10.1007/s12576-017-0535-y
|View full text |Cite
|
Sign up to set email alerts
|

Sweet taste receptor in the hypothalamus: a potential new player in glucose sensing in the hypothalamus

Abstract: The hypothalamic feeding center plays an important role in energy homeostasis. The feeding center senses the systemic energy status by detecting hormone and nutrient levels for homeostatic regulation, resulting in the control of food intake, heat production, and glucose production and uptake. The concentration of glucose is sensed by two types of glucose-sensing neurons in the feeding center: glucose-excited neurons and glucose-inhibited neurons. Previous studies have mainly focused on glucose metabolism as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…There is also a strong evidence suggesting the importance of the brain-gut axis in regulating pancreatic secretion (Konturek et al, 2003;Jaworek et al, 2010). Interestingly, sweet/amino acid receptors also are located in the hypothalamus (Heeley and Blouet, 2016;Kohno, 2017) which likely are important in sensing systemic glucose and amino acid concentrations and along with neural and hormonal signals are sensed by the hypothalamus which allows for coordinated central control of metabolism, including intestinal and pancreatic function. Other hormones thought to influence pancreatic exocrine and intestinal function either directly or through neural signals include melatonin, C-natriuretic peptide, endocannabinoids and leptin to name a few (Chandra and Liddle, 2009).…”
Section: Mechanisms Regulating the Nutritional Modulation Of Digestivmentioning
confidence: 99%
“…There is also a strong evidence suggesting the importance of the brain-gut axis in regulating pancreatic secretion (Konturek et al, 2003;Jaworek et al, 2010). Interestingly, sweet/amino acid receptors also are located in the hypothalamus (Heeley and Blouet, 2016;Kohno, 2017) which likely are important in sensing systemic glucose and amino acid concentrations and along with neural and hormonal signals are sensed by the hypothalamus which allows for coordinated central control of metabolism, including intestinal and pancreatic function. Other hormones thought to influence pancreatic exocrine and intestinal function either directly or through neural signals include melatonin, C-natriuretic peptide, endocannabinoids and leptin to name a few (Chandra and Liddle, 2009).…”
Section: Mechanisms Regulating the Nutritional Modulation Of Digestivmentioning
confidence: 99%
“…There is also evidence in mammals for GK-independent glucosensing mechanisms. These include (1) enhanced expression of liver X receptor (LXR) (Mitro et al 2007, Kruse et al 2017, (2) activation of intracellular signalling cascade by sweet taste receptors (Herrera Moro Chao et al 2016, Kohno 2017, (3) enhanced expression of sodium/glucose co-transporter 1 (SGLT-1) (González et al 2009, Thorens 2012) and (4) increased expression of uncoupling protein 2 (UCP2) in response to mitochondrial production of reactive oxygen species (ROS) (Beall et al 2010, Diano & Horvath 2012. Evidence obtained in recent years also supported the presence in fish hypothalamus of comparable glucosensing mechanisms (Fig.…”
Section: Glucosementioning
confidence: 99%
“…Although taste receptors were initially discovered in taste buds, a growing number of studies have demonstrated that sweet taste receptors are expressed throughout the body, including the nasal epithelium, respiratory system, pancreatic islet cells, and even in sperm and testes [ 12 , 13 , 14 ].…”
Section: Chemosensory Cells In the Gi Tractmentioning
confidence: 99%